L'idée de droit naturel à la lumière de la sociologie juridique de Max Weber - Coutu, Michel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
Max Weber's Sociologyof Law provides, according to the author, a strong basis for understanding and discussing not only modern natural law but also contemporary human rights law. In the first part of this article, Weber's sociological analysis of natural law is briefly outlined, mainly in relation to the opposition between formal and material rationality of law. In the Weberian perspective, the antinomy between formal and material natural rights plays a key role in understanding the decline of natural law, and partly explains the irresistible rise of a purely positivistic conception of law. The second part of the study shows how the idea of natural law is in itself inconsistent with Max Weber's epistemological positions. For the author, the Sociology of Law remains closely connected to these positions, which form the basis of the Weberian methodology of (value-free) scientific research. In conclusion, the author emphasizes the importance of Weberian epistemology for the understanding of natural law and, to a certain extent, of contemporary human rights law. He raises doubts, however, as to whether legal positivism can provide a proper comprehension of recent trends in contemporary human rights law. He then suggests that the positivistic conclusion of the Sociology of Law should be reconsidered in light of the reemergence of value-rationality as a basic principle of democratic legal order.